Epidemiological Study of Meningitis Cases Admitted to AL-Razi Hospital in Diyala Governorate for the Period 2000 – 2004 - Hassan , Abdulsalam H (Diyala Journal of Medicine, 2019)
Background: Meningitis is an inflammation of the meninges (pia and arachnoids membranes) which covers the brain, it may be either a cute or chronic, purulent or a septic (sterile). Meningitis may be caused by infection with viruses , bacteria or other microorganism Patients & method: A review of case records of patients with meningitis admitted to Al_razi hospital in Diyala governorate for the period the 1st of january 2000 to the 31th of December 2004 inclusive .Data were collected from the case records according to especial designed questionnaire . Analysis of the collected data was done and the results of this descriptive study presented by numbers and percentages. Results: Meningitis was the first cause of admittion (56.6%),meningitis more in males with M:F ratio 1.5:1,more than 85%cases occurred in those below 19 years age ,most cases were rural residents(53.8%),more than 50% of cases reported in spring and autumn, meningitis reported mostly in students 72%,viral meningitis form 54.5%,case fatality rate was 6.3%. Conclusion: Meningitis is the first cammon cause of admission and there must be a good efferts to decrease morbidity and mortality of this disease